At the Crossroads of Autonomy and Essentialism: Indigenous Peoples in International Environmental Politics - Lindroth, Marjo; Sinevaara-Niskanen, Heidi (International Political Sociology, 2013)
Indigenous peoples are often perceived as custodians of nature owing to their close relationship with their environment and their nature-based livelihoods. This paper investigates the kinds of environmental agencies that are constructed for, and by, indigenous peoples within the United Nations (UN) Permanent Forum on Indigenous Issues (PF) and the Arctic Council. The particular focus of this research is the issue of responsibility. The article brings together empirical materials from the two forums and engages with them using Foucault-inspired approaches. We offer a critical discussion of indigenous peoples' environmental agency in international politics, addressing the need to problematize representations of indigenous agency that to date have been largely unchallenged in both the practice and study of international politics. We identify three perspectives through which the environmental agency of indigenous peoples is validated and justified: having particular knowledge, being stakeholders, and having a close relationship with nature. Certain kinds of expectations are inscribed in each of these perspectives; responsibility becomes intertwined with agency.